Long‐term effect of HCV eradication in patients with mixed cryoglobulinemia: A prospective, controlled, open‐label, cohort study. Issue 4 (10th February 2015) - Gragnani, Laura; Fognani, Elisa; Piluso, Alessia; Boldrini, Barbara; Urraro, Teresa; Fabbrizzi, Alessio; Stasi, Cristina; Ranieri, Jessica; Monti, Monica; Arena, Umberto; Iannacone, Claudio; Laffi, Giacomo; et al.
Abstract : Limited data are available about the efficacy of antiviral treatment in hepatitis C virus (HCV)–associated mixed cryoglobulinemia (MC), especially concerning the long‐term effects of HCV eradication. The aim of this study was to evaluate the influence of MC on the virological response and the long‐term effects of viral eradication on MC. We prospectively enrolled 424 HCV + patients belonging to the following groups: MC syndrome (MCS)‐HCV (121 patients with symptomatic MC), MC‐HCV (132 patients with asymptomatic MC), and HCV (158 patients without MC). Pegylated interferon plus ribavirin treatment was administered according to standard protocols. Posttreatment follow‐up ranged from 35 to 124 months (mean 92.5 months). A significant difference was observed in the rate of sustained virological response between the HCV group and both the MC‐HCV ( P = 0.009) and MC‐HCV+MCS‐HCV ( P = 0.014) groups. Multivariate logistic regression analysis identified cryoglobulinemia as an independent prognostic factor of nonresponse. The clinical–immunological response in MCS‐HCV correlated with the virological one. All patients with sustained virological response also experienced a sustained clinical response, either complete or partial. In the majority of sustained virological response patients all MCS symptoms persistently disappeared (36 patients, 57%); in only two (3%) did definite MCS persist. All virological nonresponders were also clinical nonresponders, in spite of a transient improvement in some cases. No evolution to lymphoma was observed. For the first time we have evaluated both the effects of interferon‐based therapy on HCV patients with and without MC and with and without symptoms, as well as the long‐term effects of viral eradication on MC. Conclusion : MC is a negative prognostic factor of virological response. Clearance of HCV led to persistent resolution or improvement of MCS, strongly suggesting the need for a next generation of highly effective antiviral drugs. (Hepatology 2015;61:1145‐1153)